MILLENNIAL CUSTOMER LOYALTY IN ONLINE SHOPPING ON DIGITAL PLATFORMS: A PERSPECTIVE OF NET PROMOTER SCORE - Slamet Slamet; Findi Dia Finalia Sari; Indrayati Indrayati; Ilya Azmala (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2021)
This study maps and analyses the customer loyalty level, namely, the Millennials aged 23-38 shopping online through digital platforms in 2020. The study's objects include, Bukalapak.com, Shopee.co.id, Tokopedia.com, Bibbli.com, Lazada.co.id, Carrefour.co.id, Indomaret.com, Zalora.co.id, Tiket.com, Traveloka.com, Gojek.com, Grab.com, and Gopay.com. The survey was conducted in Malang City and Regency, Indonesia. The instrument used was a questionnaire containing the respondent's profile and a single question about the willingness to offer recommendations to friends or colleagues. The questionnaire was circulated using Google Forms through WhatsApp and email. Furthermore, descriptive statistical analysis was used to describe the data in percentage, while the Net Promoter Score (NPS) method was used to determine customer category. The results showed that most consumers using the digital platform were in the Detractor (46.15%), including Lazada.co.id (NPS=-1.30%), Tiket.com (NPS-1.80%), Carrefour.co.id (NPS=-3.66%), Zalora.co.id (NPS=-3.68%), Bukalapak.com (NPS=-12.03), and Blibli.com (NPS=-18.13%). It means those platforms have disloyal consumers due to poor service. The second level is in the Passive category (38.46%), including Gojek.com (NPS=39.48%), Traveloka.com (NPS=32.92%), Tokopedia.com (NPS=23.82%), Gopay.com (NPS=23.4%), and Indomaret.com (NPS=22.91%). It means their services are satisfactory. Only 15.38% of consumers are in the Promoter, namely Shopee.co.id (NPS=53.86%) and Grab.com (NPS=56.32%). The services of these platforms are excellent, and their customers are very loyal. Thus, based on the NPS method, digital platform users in Indonesia are mostly Detractor and Passive users, very few in the Promoter category.